2011
DOI: 10.1118/1.3549764
|View full text |Cite
|
Sign up to set email alerts
|

Experience of micromultileaf collimator linear accelerator based single fraction stereotactic radiosurgery: Tumor dose inhomogeneity, conformity, and dose fall off

Abstract: Tumor dose inhomogeneity can be used as an important and convenient parameter to evaluate mMLC LINAC-based SRS plans. Sharp dose fall off in the normal tissue is achieved with sufficiently high tumor dose inhomogeneity. By adjusting beam margins, a homogeneity index of approximately 1.3 would provide best conformity for the authors' SRS system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 46 publications
0
30
0
2
Order By: Relevance
“…The associated steep dose fall off degrades the dose coverage disproportionately for small tumors, requiring an increase in the block margin, as shown in Figure 7. A similar trend with rapid fall in the homogeneity index (=maximum PTV dose/Rx dose) with increasing block margin (referred as "beam margin") was seen with the small brain lesions in a stereotactic radiosurgery study (SRS) by Hong et al 15 We found that the only method by which the volume irradiated by a certain dose level can be reduced is to prescribe to a lower isodose line as shown in Figure 8. As indicated in Figure 9, this results in an increase in the global maximum dose and the volume of all absolute dose levels.…”
Section: Discussionmentioning
confidence: 60%
“…The associated steep dose fall off degrades the dose coverage disproportionately for small tumors, requiring an increase in the block margin, as shown in Figure 7. A similar trend with rapid fall in the homogeneity index (=maximum PTV dose/Rx dose) with increasing block margin (referred as "beam margin") was seen with the small brain lesions in a stereotactic radiosurgery study (SRS) by Hong et al 15 We found that the only method by which the volume irradiated by a certain dose level can be reduced is to prescribe to a lower isodose line as shown in Figure 8. As indicated in Figure 9, this results in an increase in the global maximum dose and the volume of all absolute dose levels.…”
Section: Discussionmentioning
confidence: 60%
“…Not only did we demonstrate the feasibility of AV node ablation using SRS, but our results also establish the safety of this cardiac radioablation procedure, at least in pigs, with no radiation injury detected in nearby healthy tissues. The radiation dose falloff in SRS is around 10% to 15% per millimeter, with a resulting dose falloff of 50% at 2 to 5 mm, with only 0.05% of the dose remaining at 1 m from the target lesion . Therefore, SRS is associated with a sharp falloff in radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…For Cyberknife, the value of P‐IDL is often between those values . Previous studies showed that using either noncoplanar conformal static field or dynamic conformal arcs the optimal P‐IDL is around 77%. With development of volumetric arc therapy (VMAT) technique on LINAC, in which the beams are modulated for dose rate, MLC aperture and gantry angle continuously, more variables are introduced in the inverse planning and delivery process for SRS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…SRS treatment for brain tumors requires conformity in both high and intermediate dose regions for better sparing normal brain tissue. The toxicities of SRS have been linked to V12, the volume of brain tissue irradiated with 12 Gy and conformity index . The dose prescription practice differs significantly among the modalities: Gamma Knife, Cyber Knife, and LINAC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation